Rozwiązania techniczne i materiały zastosowane przy zabezpieczeniu skarpy zbiornika wodnego w Dychowie = Technical solutions and the materials used in protecting the slope of the water reservoir in Dychow - Grzelak, Krzysztof (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
On December 23rd, 1997 the electric energy generared by the Hydro-Electric Power Station in Dychów reached the National Electric Power Engineering system after the upper reservoir embankments have been reconstructed and modernized. The works had been carried outcontinuously since April 23rd, 1997 when the upper reservoir slope including the national road No 287 had slid down onto the premises of the Hydro-Electric Power Station Dychów. Around 30 thousand cubic meters of ground had been relocated. The building wall of the power station had been destroyed, the technological facilities in the turbine sef l as well as the electric and control apparatus had been covered with earth.
Keywords: Dychów; elektrownie wodne; badania